2015
DOI: 10.1038/srep14362
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating p22phox ameliorates inflammatory response in Angiotensin II-induced oxidative stress by regulating MAPK and NF-κB pathways in ARPE-19 cells

Abstract: Oxidative stress and inflammation are two interrelated biological events implicated in the pathogenesis of many diseases. Reactive oxygen species (ROS) produced under oxidative stress play a key role in pathological conditions. Inhibition of p22phox, an indispensable component of the NADPH oxidase (NOX) complex comprising the main source of ROS, plays a protective role in many ocular conditions by inhibiting the activation of NOXs and the generation of ROS. However, little is understood regarding the role of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…In the present study, the alterations of rat liver p22 phox levels were found to be compatible with the NF-κB levels change. As a corresponding mechanistic proposition for our results, the downregulation of p22 phox was reported to be closely connected with the suppression of the mitogen-activated protein kinase (MAPK) and NF-κB pathways (Qiu et al, 2015).…”
Section: F I G U R Esupporting
confidence: 67%
“…In the present study, the alterations of rat liver p22 phox levels were found to be compatible with the NF-κB levels change. As a corresponding mechanistic proposition for our results, the downregulation of p22 phox was reported to be closely connected with the suppression of the mitogen-activated protein kinase (MAPK) and NF-κB pathways (Qiu et al, 2015).…”
Section: F I G U R Esupporting
confidence: 67%
“…For instance, studies involving down-regulation of the gene encoding the p22phox enzyme, which produces reactive oxygen species, shows antiinflammation effect in ARPE-19 cells by regulating MAPK and NF-κB pathways. 104 These studies support the notions that p22phox plays an important role in inflammation accompanied by oxidative stress and implies that p22phox may provide a novel therapeutic target for oxidative induced…”
Section: Concluding Remarks and Future Considerationsmentioning
confidence: 57%
“…The increased NADPH oxidase expression mediates blood pressure increase and contributes to ROS production, endothelial dysfunction, inflammation and increased extracellular matrix (ECM) deposition in vascular tissues (Bruder‐Nascimento et al., ; Dikalov et al., ; Kim et al., ; Murdoch et al., ). It has been reported that inhibition of NADPH oxidase expression attenuated blood pressure increase, endothelial dysfunction and vascular remodelling in AngII‐induced hypertensive rats (Bruder‐Nascimento et al., ; Dikalov et al., ; Murdoch et al., ; Qiu et al., ). Of note, accumulating data have shown that AngII acutely increased NADPH oxidase activity without change in NADPH oxidase expression in vascular endothelial cells and vascular smooth muscle cells (Seshiah et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…that inhibition of NADPH oxidase expression attenuated blood pressure increase, endothelial dysfunction and vascular remodelling in AngII-induced hypertensive rats (Bruder-Nascimento et al, 2014;Dikalov et al, 2014;Murdoch et al, 2011;Qiu et al, 2015). Of note, accumulating data have shown that AngII acutely increased NADPH oxidase activity without change in NADPH oxidase expression in vascular endothelial cells and vascular smooth muscle cells (Seshiah et al, 2002).…”
mentioning
confidence: 98%